Dietary outcomes of community-based CVD preventive interventions: a systematic review and meta-analysis - Hamid Y Hassen; Binyam G Sisay; Jean-Pierre Van Geertruyden; Delphine Le Goff; Rawlance Ndejjo; Geofrey Musinguzi; Steven Abrams; Hilde Bastiaens (Public Health Nutrition, 2023)
Abstract